The Effect Of Promotion On Sales Of Oreo Products At PT. Mondelez Indonesia Pekanbaru - Jeli Nata Liyas (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The purpose of this study was to determine the effect of promotion on sales of oreo products at PT. Mondelez Indonesia Pekanbaru. The population in this research is shop customers of PT. Mondelez Indonesia Pekanbaru totaling 287 people. The sample in this study amounted to 74 shop customers with a sampling technique using the slovin formula. The type of data used is primary data sourced from questionnaires. Data analysis using simple linear regression. The result of the regression equation is Y = 8.541 + 1.106 X. From the results of the t test, it is obtained that t count (14.861) > t table (1.993) and a sig value of 0.000 <0.05, then Ho is rejected and Ha is accepted, meaning that promotion has a significant effect on sales. The result of the coefficient of determination R2 is 0.754. This shows that sales (the dependent variable) are affected by 75.4% by promotions (the independent variable), while the remaining 24.6% are influenced by other variables outside this study.